Hypoxanthine Induces Muscular ATP Depletion and Fatigue via UCP2 - Yin, Cong; Ma, Zewei; Li, Fan; Duan, Chen; Yuan, Yexian; Zhu, Canjun; Wang, Lina; Zhu, Xiaotong; Wang, Songbo; Gao, Ping; Shu, Gang; Zhang, Huihua; et al. (Frontiers in Physiology, 2021)
Hypoxanthine (Hx), intermediate metabolites of purine metabolism pathway, dramatically increased in blood and skeletal muscle during muscle contraction and metabolism, is characterized as a marker of exercise exhaustion. However, physiological effects of Hx on skeletal muscle remain unknown. Herein, we demonstrate that chronic treated with Hx through the dietary supplementation resulted in skeletal muscle fatigue and impaired the exercise performance of mice without affecting their growth and skeletal muscle development. Hx increased the uncoupling protein 2 (UCP2) levels in the skeletal muscle, which led to decreasing energy substrate storage and enhanced glycolysis. These effects could also be verified in acute treated with Hx through intraperitoneal injection. In addition, muscular specifically knockout of UCP2 through intra-muscle tissue injection of adenovirus-associated virus reversed the effects of Hx. In conclusion, we identified a novel role of Hx in the skeletal muscular fatigue mediated by UCP2-dependent mitochondrial uncoupling. This finding may shed light on the pathological mechanism of clinical muscle dysfunctions due to abnormal metabolism, such as muscle fatigue and weakness.